Effects of grazing system on performance of cow-calf pairs grazing bermudagrass pastures interseeded with wheat and legumes - Lomas, Lyle W.; Moyer, Joseph L.; Coffey, K.P.; Milliken, George A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 96 fall-calving cows and 64 calves grazed bermudagrass interseeded with wheat and legumes during 1996, 1997, and 1998 in either a continuous or rotational system stocked at equal rates. Legume cover, available forage dry matter, residual hay production, gains of cows and calves grazing wheat interseeded into bermudagrass, and gains of cows grazing bermudagrass interseeded with legumes were measured. Grazing system had no effect on legume cover, available forage dry matter, gains of cows and calves (wheat phase), and gains of cows (legume phase); however, rotationally grazed pastures produced more residual hay than those grazed continuously.
Keywords: Beef; Interseeding; Wheat; Legumes; Grazing